Gambaran Kadar Glukosa Darah Sewaktu pada Kalangan Biksu Buddhis di Kota Jakarta Barat dan Jakarta Pusat pada Tahun 2022 - Arya Elbert Neil; Gracia J.M.T Winaktu; Rebecca Noerjani Angka; Luciana Budiati Sutanto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
The lacto-ovo vegetarian diet (VLO) is a diet consisting of plant-based foods such as vegetables, fruit and accompanied by the consumption of eggs and milk. There are many benefits of this diet, such as maintaining blood glucose levels, body fat levels, body weight, body mass index, pancreatic beta cell performance which can maintain normal blood glucose levels. This research was conducted at the Ekayana Arama Temple in West Jakarta and the Mahayana Temple which is located in Central Jakarta. The method for this research is descriptive research with cross sectional study using purposive sampling method. The results of the study consisted of 19 men and 12 women with 21 years as the youngest age and the oldest age is 77 years. The conclusion of this study is that the hypothesis is accepted, the lacto-ovo vegetarian diet can maintain blood glucose levels remain normal, mean 115.84 mg/dL with a minimum value of 82 mg/dL and 164 mg/dL as the maximum value.